Effectiveness of the Friday Court Program in the Prevention of Fraud Crimes at Mojokerto Police - Febryan, Mochamad Aldy (Indonesian Journal of Police Studies, 2024)
This study discusses the effectiveness of the "Jumat Curhat" program in preventing fraud crimes at the Mojokerto Police Resort. This program is designed as an effort to increase public trust in the Indonesian National Police and their awareness of fraud. Using a qualitative approach and program evaluation, this research aims to describe the "Jumat Curhat" program, evaluate its effectiveness in preventing fraud, and identify forms of crime prevention within the program. The results show that fraud cases in the jurisdiction of the Mojokerto Police Resort have decreased, indicating the adequate effectiveness of the "Jumat Curhat" program. Fraud prevention is achieved through two-way communication between the police and the community, which increases awareness, reduces fraud cases, strengthens relationships, and enhances understanding of crime trends. Thus, the "Jumat Curhat" program at the Mojokerto Police Resort is proven effective in preventing fraud crimes.